Effectiveness of Different Physical Activities toward Glycemic Control in Prediabetes Mellitus Clients - Arwani Arwani; Budi Widiyanto; Sri Widiyati (Poltekkes Kemenkes Semarang, 2023)
Background: the proportion of people with prediabetes is 2-4 times higher than the proportion of people with diabetes. One of the prevention efforts is through physical activity. Several studies have shown that physical activity has a significant effect on glycemic control.Purpose: this study aims to determine the effectiveness of different physical activities to glycemic control in prediabetic clients in Semarang municipality.Methods: a randomized control trial (RCT) with a pretest-posttest design was conducted on 60 prediabetic clients using different treatments (healthy / slow walking, brisk walking, combination of both slowly and brisk walking). An initial measurement (pretest) of glycemic control was carried out using an indicator of HbA1c levels and was remeasured (posttest) after 3 months.Results: the average level of glycemic control (HbA1c levels) before intervention in the healthy walking group was 5.57% and decreased to 5.46% after intervention; the combination group decreased from 5.93% to 5.78%, and in the slowly walking group decreased from 5.74% to 5.71%. However, there was no significant effect of slowly walking on glycemic control (HbA1c levels). Meanwhile, brisk walking and combination of slowly walking and brisk walking had a significant effect on glycemic control (HbA1c levels) (p0.05).Conclusion: the combination of physical activity group (brisk walking and slowly walking) has a better effect on glycemic control (HbA1c levels).